2018
DOI: 10.1159/000494250
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Continued Administration of Low-dose Aspirin for Intraoperative Bleeding Control in Gastric Endoscopic Submucosal Dissection

Abstract: <b><i>Background:</i></b> The use of antithrombotic agents for the prevention of cerebro-cardioembolic events has increased, and recent guidelines have recommended the continued administration of low-dose aspirin (LDA) during endoscopic procedures with a high risk of bleeding. However, the influence of LDA on intraoperative bleeding control status during Endoscopic submucosal dissection (ESD) remains unclear. <b><i>Methods:</i></b> We examined 293 consecutive pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…To minimize bleeding risk, compliance with guidelines for antithrombotic therapy management is advised. Although an extensive revision of antithrombotic therapy management is outside of the scope of this technical review, it is important to state that ESD should not be performed in patients receiving thienopyridine therapy since this is associated with a higher post-procedural bleeding (PPB) risk (~25 %) [ compelling evidence suggests that low dose aspirin does not significantly increase IPB/PPB risk while its discontinuation is associated with a significantly higher risk of thrombotic events (Table 2 s) [89].…”
Section: Intraprocedural Bleedingmentioning
confidence: 99%
“…To minimize bleeding risk, compliance with guidelines for antithrombotic therapy management is advised. Although an extensive revision of antithrombotic therapy management is outside of the scope of this technical review, it is important to state that ESD should not be performed in patients receiving thienopyridine therapy since this is associated with a higher post-procedural bleeding (PPB) risk (~25 %) [ compelling evidence suggests that low dose aspirin does not significantly increase IPB/PPB risk while its discontinuation is associated with a significantly higher risk of thrombotic events (Table 2 s) [89].…”
Section: Intraprocedural Bleedingmentioning
confidence: 99%
“…There have been several studies of endoscopic submucosal dissection (ESD) on continuous low dose aspirin since the previous version of this guideline. One retrospective multicentre study 87 for colonic ESD, and six retrospective studies of gastric ESD, [88][89][90][91][92][93] comparing continuation with interruption of aspirin, found no significant differences in delayed bleeding the two groups. This was confirmed by two meta-analyses which also reported that continuation of low dose aspirin does not increase the postprocedure bleeding after ESD.…”
Section: Endoscopic Submucosal Dissectionmentioning
confidence: 98%
“…There have been several studies of ESD on continuous low dose aspirin since the previous version of this guideline. One retrospective multicentre study [87] for colonic ESD, and 6 retrospective studies of gastric ESD [88][89][90][91][92][93], comparing continuation with interruption of aspirin, found no significant differences in delayed bleeding the two groups. This was confirmed by two meta-analyses which also reported that continuation of low dose aspirin does not increase the post procedure bleeding after ESD [94,95].…”
Section: Endoscopic Submucosal Dissectionmentioning
confidence: 99%